Rendering Affective Atmospheres: The Visual Construction of Spatial Knowledge About Urban Development Projects - Sophie Mélix; Gabriela Christmann (Urban Planning, 2022)
Renderings are digital visualisations of urban development projects in the field of urban design that aim to create spatial knowledge about future-built urban environments, which we also refer to as imaginaries. In our contribution, we ask how visual artists design renderings, how they try to influence spatial knowledge about future urban spaces, and in which processes renderings are produced. Using the cases of the Eko Atlantic City project in Lagos (Nigeria) and the Hudson Yards project in New York City (USA) as examples, it will be shown empirically how specialized visual artists try to make urban development projects appear convincing and appealing. The analyses show that visual artists particularly use design elements such as photorealistic aesthetics and lighting to make the presentations of the planned building projects desirable. They also attempt to make them appear coherent in their built environment by digitally collaging different imaginary elements. Interestingly, only a limited number of image types are used. They can nevertheless put the imaginary space of the planned building projects in a positive light, create pleasant affective atmospheres, and appeal to a wide audience. By visually constructing imaginaries about urban development projects and thus influencing the subjective spatial knowledge of stakeholders and a broader public, renderings develop power. The constructed—and widely shared—imaginary space can guide investment and influence planning processes and the materialization of the built project.
Keywords: 710; digitalization; Lagos; New York; spatial imaginaries; urban design; visualizations